Religion and the making of modern East Asia - DuBois, Thomas David (New approaches to Asian history, 2011)
"Religion and religious ideas have played a fundamental role in the shaping of Asian history, society, and cultural practices. In this engaging and informative book, Thomas David DuBois sets out to explain how religious traditions and philosophies in China and Japan have evolved and intersected since the birth of Confucianism in China and the arrival of Buddhism in Japan. Crossing a broad terrain from Tokyo to Tibet, the book concentrates on the post-fourteenth century, when the long-lasting political dynasties that transformed the political, social, and economic institutions of both countries came into being. It is these connections that the author is keen to highlight, and he does so to effect by using key moments, such as the Taiping Uprising and the Boxer Rebellion, to underscore the importance of religion in transforming the course of Asian history. Contemporary chapters reflect on the wartime deification of the Japanese emperor, Marxism as religion, and the persecution of the Dalai Lama"--